Nicotine, propylene glycol and tobacco-specific nitrosamines content in selected e-liquids in Malaysia: the case support for initiation of standards or guidelines - Zulkifli, Aziemah; Zainal Abidin, Emilia; Zainol Abidin, Najihah; Mohd Ghazali, Hasanah; Praveena, Sarva Mangala; Amer Nordin, Amer Siddiq; Syed Ismail, Sharifah Norkhadijah; Rasdi, Irniza; Karuppiah, Karmegam; Abdul Rahman, Anita; Musbah, Zuraidah; Zulkipli, Nur Fadhilah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2018)
Introduction: Electronic Cigarette (EC) usage has been gaining acceptance in Malaysia despite its lack of analytical evidence on the chemical constituents of its liquid formulations. This study aims to evaluate the chemical concentrations of nicotine, propylene glycol (PG) and selected Tobacco-Specific Nitrosamines (TSNAs); 4-(methylnitrosa-mino)-1-(3-pyridyl)-1-butanone (NNK) and N’-nitrosonornicotine (NNN) in e-liquids locally sourced from the Malaysian market. Methods: A total of 17 e-liquids from a variety of flavours and brands were purchased from local EC retailers in Klang Valley, Malaysia. Nicotine and PG concentrations were assessed using Gas Chromatography-Flame Ionization Detector (GC-FID) while NNK and NNN were quantified using Liquid Chromatography-Tandem Mass Spectrometry (LC-MS/MS). The concentrations of nicotine and PG (mg/mL) were described in comparison with the levels indicated on the labels when present while levels of TSNAs were descriptively explained. Results: Nicotine was detected in all e-liquid samples, despite several samples being declared as nicotine-free. The average (standard deviation) level of nicotine, PG, NNN and NNK were 3.26 (1.04) mg/mL, 484.10 (98.24) mg/mL, 0.383(0.288) μg/L and 0.086 (0.057) μg/L, respectively. Labelling discrepancies (when indicated on the label) of nicotine and PG were between the range of 27%-73% and 3%-63%, respectively. Conclusion: The concentrations of nicotine and PG in local e-liquids were varied. There were evidences of labelling discrepancy in that local e-liquids. TSNAs were detected in all samples of e-liquids. This study brought forth strong evidence on the need for the implementation of regulation on e-liquid manufacturing and sales, particularly on the accuracy of labelling and licensing to protect the public health.